Critical power of knee extension exercises does not depend upon maximal strength - Le Chevalier, J. M.; Vandewalle, H.; Thepaut-Mathieu, C.; Pujo, M.; Le Natur, B.; Stein, J. F. (European Journal of Applied Physiology, 2000)
A possible dependence of critical power (CP) and the Y-intercept of the work/exhaustion time relationship (Yintercept) on maximal muscular strength of the same muscle group has been studied in nine endurance-trained subjects, seven gymnasts, and seven weight-lifters. CP was calculated as being equal to the slope of the linear relationship between exhaustion time and the work performed at exhaustion on a knee extension ergometer. Yintercept was equal to the intercept between this relationship and the work axis. The muscular strength of the knee was evaluated by measuring the torques exerted on a Biodex knee isokinetic dynamometer at four angular velocities: 0° · s-1 (T0), 90° · s-1 (T90), 180° · s-1 (T180) and 240° · s-1 (T240). The results of the present study do not support the hypothesis that CP depends upon maximal strength. Indeed, CP was not correlated with T0, T90, T180 or T240 (|r| < 0.01). Yintercept was significantly and positively correlated only with T90.